The VISCACHA survey – V. Rejuvenating three faint SMC clusters. Issue 1 (15th September 2022) - Bica, E; Maia, F F S; Oliveira, R A P; Dias, B; Santos, J F C; Rocha, J P; Kerber, L; Gardin, J F; Armond, T; Parisi, M C; Souza, S O; Barbuy, B
ABSTRACT: We present the analysis of three faint clusters of the Small Magellanic Cloud RZ 82, HW 42, and RZ 158. We employed the SOAR telescope instrument SAM with adaptive optics, allowing us to reach to V ∼ 23–24 mag, unprecedentedly, a depth sufficient to measure ages of up to about 10–12 Gyr. All three clusters are resolved to their centres, and the resulting colour–magnitude diagrams (CMDs) allow us to derive ages of 3.9, 2.6, and 4.8 Gyr, respectively. These results are significantly younger than previous determinations (7.1, 5.0, and 8.3 Gyr, respectively), based on integrated photometry or shallower CMDs. We rule out older ages for these clusters based on deep photometry and statistical isochrone fitting. We also estimate metallicities for the three clusters of [Fe/H]=-0.68, −0.57, and −0.90, respectively. These updated ages and metallicities are in good agreement with the age-metallicity relation for the bulk of SMC clusters. Total cluster masses ranging from 7\!-\!11· 10^3 M_ were estimated from integrated flux, consistent with masses estimated for other SMC clusters of similar ages. These results reduce the number of SMC clusters known to be older than about 5 Gyr and highlight the need of deep and spatially resolved photometry to determine accurate ages for older low-luminosity SMC star clusters.